A combined optimization with multivariable active disturbance rejection control strategy applied to microalgae continuous culture (2024)
The cultivation of microalgae in closed photobioreactors offers several advantages, including precise control over temperature, pH, and light distribution, as well as reduced contamination risks. Microalgal species that have achieved successful large-scale commercial production include Spirulina (Arthrospira), Dunaliella, Chlorella, and Haematococcus. Nevertheless, the potential for yielding various bioactive compounds for pharmaceuticals and nutraceuticals applications in other species remains largely in the preclinical stage or confined to laboratory settings for other applications. Consequently, commercial products derived from microalgae are relatively scarce.